Shining Light on Labels in the Dark: Guidelines for Offensive Collections Materials. Issue 4 (December 2022) - Briscoe, Laura; Nazaire, Mare; Allen, J. Ryan; Baker, Janelle; Donnell Davenport, Aliya; Mansaray, Janet; McCormick, Carol Ann; Santiago Coyle, McKenna; Schmull, Michaela
The natural history collections community has made significant strides in the past decade in the digitization of their holdings. Digitization has made the data and corresponding images of collections publicly available to researchers, students, and the public. Data and images are served online by institutions' local databases, and regional, national, and international aggregators. One challenging aspect in digitizing natural history collections is the presence of offensive language, such as racial slurs in collection and location data. We present findings from a community survey and analysis of data from relevant aggregators to assess the presence of and approach to offensive language in collections data. We also suggest initial guidelines for data warning statements and disclaimers and transcription guidelines to help preserve historical integrity of data while also supporting inclusive and safe workspaces. Please note that in writing about offensive terms found in natural history collections, we use and refer to offensive terms and include images of labels and documents to provide examples.